How did the Teachers Talk? Investigating Politeness Strategies in Teachers’ Utterances during Classroom Interactions in English Subject - Febrina Amanda Putri; Ikke Dewi Pratama (Universitas Sebelas Maret, 2023)
Analyzing politeness strategies in classroom interaction can reveal the communications between teachers and students during classes. Furthermore, it can reflect the relationship of both parties and thus can be used as a mean to improve the quality of the teaching-learning process. This research is conducted to analyze the types of politeness strategies found in the teachers’ utterances in English teaching-learning process. Observations are conducted in two English classes at one of public schools in Karanganyar, Central Java, Indonesia. The subjects of the research are two English teachers. The data were analyzed using data reduction, data display, conclusion, and verification. The data were classified under the theory of politeness strategies as proposed by Brown and Levinson. The results revealed that the English teachers performed four types of politeness strategies with a total of 239 data. The different dominant politeness strategies from the two teachers showed that the intentions aimed by the teachers in classroom interactions are different. The first teacher showed the use of bald on record strategy as the dominant strategy showing the emphasis on directness and the use of simple utterances. Meanwhile, the second teacher tended to use politeness strategy to show closeness and friendliness to the students.